Impact of the MFA phase-out on the world economy: an intertemporal global general equilibrium analysis - Diao, Xinshen; Somwaru, Agapi (International Food Policy Research Institute, 2001)
This study focuses on the possible impact of the MFA phase-out on the world economy. Starting from analyzing trends in world textile and apparel trade, the study found that the developing countries were a growing factor in world T&A trade in recent decades. Moreover, using trade data from 91 countries over 37 years, the study indicates a strong positive relationship between trade in textile and apparel and the standard of living. The study further focuses on the possible impacts of the MFA phase-out on the world T&A using an intertemporal, global general equilibrium model. The study found the the MFA phase-out would enlarge world trade of T&A and developing countries will further gain market share in world total exports. Even though the developing countries currently free from the MFA quota restraints may lose their market shares, as world T&A prices are lowered by improving the efficiency of world T&A trade post-MFA, consumers are better off by consuming cheap commodities.